The barracuda model in handling anarchic demonstrations - Iskandar, Taufik (Linguistics and Culture Review, 2021)
This study aims to find out (1). Anarchist demonstrations (2). How to control anarchist demonstrations (3). Model faces demonstration. The research method is a qualitative approach, to describe the demonstration case. Data collection techniques through questionnaires, observations, interviews, and documentation studies. The data sources used are primary and secondary. Conclusion: (a). Anarchist demonstration is a superficial understanding of issues, demands, with collective expression and action. (b). Strategic analysis can control anarchist actions (c). Barracuda model brain, arrival, and action, as an alternative solution to reduce demonstrations.